Won't cry over spoilt milk : Amul's response to customer's complaint on social media - Abhishek (London : SAGE Publications Ltd, 2017)
Ms. Neha Tomar, Senior Legal officer, working with Public Health Foundation of India (PHFI) at Gurgaon, published a post on Facebook which provided details of her bizarre experience with Amul Gold milk. She claimed that the milk turned into awful looking stretchy dough when she heated it. In the post, Neha requested everyone to stop taking Amul milk and asked authorities to take strict and stringent actions against Amul. This news created a flutter as Amul was known to maintain the highest standards and the brand had come to symbolize quality in milk products category.
Originally published: Abhishek (2014). Won't Cry Over Spoilt Milk: Amul's Response to Customer's Complaint on Social Media. MAR0450. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Tomar, Neha; Amul Gold; Public Health Foundation of India; Mass media -- Political aspects -- India; Dairy products industry -- India -- Case studies; Dairy products -- Standards -- India -- Case studies